Availability of Information Resources for Visually Impaired Students in University Libraries in Nigeria: A Tool for Inclusive University Education: A Tool for Inclusive University Education - Horsfall, Millie Nne; Opara, Vincent Chima (International Journal of Knowledge Content Development & Technology, 2023)
This research investigates the availability of information resources for visually impaired students in University libraries in Nigeria; a tool for inclusive University education. A Descriptive survey research design was adopted for the study and a total number of 20 University libraries took parts in the study. A self-constructed online questionnaire was designed and distributed to collect the data from respondents (librarians) using a simple random sampling technique. A total of 45 respondents filled out the online questionnaire, but 40 were valid and useful for analysis. The use of frequency count and percentages method of data analysis was adopted for this research work. The study reveals that most of the University libraries lacked information resources for visually impaired students, it was found that the inclusion of information resources for visually impaired persons will promote inclusive education and librarians’ skills. The challenges hindering the availability of information resources to the visually impaired students are insufficient funds for maintenance, erratic power supply and inadequate skills by users, among others. Recommendations were made for the campaign for inclusive education and the provision of information resources for visually impaired students.